2022
DOI: 10.1111/epi.17199
|View full text |Cite
|
Sign up to set email alerts
|

Time to onset of cannabidiol treatment effect and resolution of adverse events in tuberous sclerosis complex: Post hoc analysis of randomized controlled phase 3 trial GWPCARE6

Abstract: Objective To estimate the timing of cannabidiol (CBD) treatment effect (seizure reduction and adverse events [AEs]) onset, we conducted a post hoc analysis of GWPCARE6 (NCT02544763), a randomized, placebo‐controlled, phase 3 trial in patients with drug‐resistant epilepsy associated with tuberous sclerosis complex (TSC). Methods Patients received plant‐derived pharmaceutical formulation of highly purified CBD (Epidiolex; 100 mg/ml oral solution) at 25 mg/kg/day (CBD25) or 50 mg/kg/day (CBD50) or placebo for 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The interpretability and generalizability of the results are limited mostly because it was a post hoc analysis of pooled data from two trials with a rigid titration schedule. Although the observation of an early/clear separation from placebo may not prove to be statistically significant in a prospectively designed trial, the evidence of an early CBD antiseizure effect in two other post hoc analyses of trials in LGS 24 and TSC 25 robustly supports our results of an early antiseizure effect in DS. We could not evaluate the by‐day onset of efficacy for patients taking versus not taking clobazam due to the small number of patients not taking clobazam combined with the highly variable seizure data from just the first few days of treatment (compared to the full 14‐week treatment period); such an analysis would require a more appropriately powered study with balanced subgroups.…”
Section: Discussionsupporting
confidence: 69%
“…The interpretability and generalizability of the results are limited mostly because it was a post hoc analysis of pooled data from two trials with a rigid titration schedule. Although the observation of an early/clear separation from placebo may not prove to be statistically significant in a prospectively designed trial, the evidence of an early CBD antiseizure effect in two other post hoc analyses of trials in LGS 24 and TSC 25 robustly supports our results of an early antiseizure effect in DS. We could not evaluate the by‐day onset of efficacy for patients taking versus not taking clobazam due to the small number of patients not taking clobazam combined with the highly variable seizure data from just the first few days of treatment (compared to the full 14‐week treatment period); such an analysis would require a more appropriately powered study with balanced subgroups.…”
Section: Discussionsupporting
confidence: 69%
“…Although the etiology is not known, diarrhea has been reported as the most frequent AE in other clinical trials of CBD; in most cases, however, the severity was mild or moderate and resolved before the end of treatment. 30 , 31 Permanent treatment discontinuation because of an AE was low (6%) despite some patients being on treatment for up to 130 weeks, supporting a favorable safety profile of CBD for long‐term use in patients with TSC‐associated seizures.…”
Section: Discussionmentioning
confidence: 94%
“…Findings from a post hoc analysis suggested that the onset of the treatment effect occurred early, within the first 2 weeks. 101 Longer-term adjunctive CBD treatment has been evaluated in an OLE to the GWPCARE6 study, involving 199 of the 201 patients who completed the RCT. 77 Reductions in seizures were maintained through 48 weeks, at least 6% of patients remained seizure free during the 12-week windows, and improvement in S/CGIC continued to be reported by a high proportion of proportion of patients/caregivers (Table 2; Figure 3).…”
Section: Cannabidiolmentioning
confidence: 99%
“…A post hoc analysis reported that AEs lasted longer for CBD versus placebo but resolved within the 16-week study in most patients. 101 Furthermore, results from a real-world study have suggested that slow titration of CBD can deliver improved tolerance with comparable efficacy. 102 The AE profile over the long-term in the OLE was similar to that observed previously.…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation